Secondary Level Students’ Experiences in English as a Medium of Instruction: A Nepalese Context - Rai, Aananda (International Journal of Language and Literary Studies, 2024)
This study explores the secondary-level students’ experiences in English as a medium of instruction in education. It aimed at identifying the challenges in English as a medium of instruction for the students in the Nepalese educational settings. It used narrative inquiry as a research method in order to explore the living experiences of the students regarding the practice of using the English language as a language of classroom instruction in the context where English is used as a non-native language. Semi-structured interview has been used as a research process for data collection and the interview guidelines have been used as research tools while collecting data from purposely selected seven student participants studying in the secondary level. This study has revealed that the students experience English as a medium of instruction as a practice to boost up their confidence personally as well as academically despite their EMI hardships in and outside their educational settings.